ChemInform Abstract: Synthesis of Acylsilanes by Copper(I)‐Catalyzed Addition of Silicon Nucleophiles onto Acid Derivatives. Issue 16 (22nd April 2014) - Cirriez, Virginie; Rasson, Corentin; Riant, Olivier
Abstract Additionally, a one‐pot two‐step procedure for the synthesis of acylsilanes directly from carboxylic acids is also presented.